Reorientasi Makna Bait Suci sebagai Tempat Ibadah Berdasarkan Interpretasi Wahyu 21:22 - Erman Sepniagus Saragih (Sekolah Tinggi Teologi SAAT (Southeast Asia Bible Seminary), 2022)
The Covid-19 pandemic has raised doubts about the sacredness of places, spaces, and materials for worship celebrations by the church. As a manifestation of God’s kingdom on earth, the church seems to reduce the space for encountering sacred and profane things with God. This article argues that even though the church is the arbitrator of the congregation with God (sacred and profane), the dynamics of the history of the Temple, the physical building is not legal-sacred worship because Christ is the final form of the Temple and believers participate in the New Jerusalem era. The conclusions are: first, the absence of an eschatological temple as part of the anti-Temple and anti-Temple polemic in various segments of Judaism and Greco-Roman, although, of course, the expectation of an eschatological temple was a reasonable expectation for early Jewish eschatology. Second, for Christians in Asia, the function of the physical Temple is not so essential in worship celebrations. However, the involvement of the container in the history of their belief is necessary. Third, John’s eschatological Temple emphasizes a new paradigm shift regarding Divine ownership in their minds, not the imagination of immortal things. Thus, the congregation as performers are not limited by symbols of worship and practicing spirituality must be able to transcend the symbols of worship from time to time.